Komm, süsser Tod bei Notruf Mord - Haas, Wolf 1960- (absolut Medien, 2000)
Thrown off the police force, former detective Brenner works as an ambulance driver in Vienna. He and the other drivers try to outwit another ambulance service to get more business. When a favorite nurse is brutally murdered, Brenner and others set out to track down the killer.
Orig.: Österreich 2000
Enth. Linkliste
Keywords: Ambulance drivers -- Austria -- Vienna -- Drama; Comedy films; Feature films; Murder -- Investigation -- Austria -- Vienna -- Drama; Wien; Österreich; Vienna (Austria) -- Drama